Geochemistry of heavy metals in bottom sediments from streams of the western coast of the Rio de La Plata estuary, Argentina - Ronco, Alicia Estela (2001)
The fluvial system within the southwestern coastal sector of the Rio de la Plata interacts with a very large and efficient mixing basin known as the Rio de la Plata estuary. The region is a densely populated and productive sector of Argentina and is characterised by a temperate humid climate. The streams Carnaval, Martin, Del Gato and El Pescado of the study area drain two main geomorphologic units: a higher inner zone and the low lands of the coastal plain. In particular, the Del Gato stream receives heavily polluted discharges from agricultural, urban and industrial point and non-point sources of pollution, while the other streams collect a lower and variable discharge input. As a part of an initial assessment of the role of fluvial bottom sediments in the fate of metals through the stream ecosystems, the spatial distribution of trace and major elements related to particles in the accumulation areas was examined. Concentration of Cr, Ni, Cu, Zn, Cd, Hg, Pb, Fe and Mn, grain size, mineralogy (clay-X ray diffraction) and organic matter content were analysed in the four streams considering both geomorphologic units at different depositional time. Untreated and iron-normalised trace metal concentrations in the most polluted streams show higher levels in the upper layers of most contaminated sectors and accumulation areas associated to topographic low lands. The coastal plain sector behaves as a regional sink between the upstream area and the estuary.